Model for Improving the Financial Management Performance of West Papua Province Based on Competence, Accountability, Organizational Commitment, and Quality of Supervision - Yohan Karubaba, Kaleb; Ansar, Ansar; Gunawan, Gunawan; Kurniawaty, Kurniawaty (Devotion : Journal of Research and Community Service, 2024)
This study aims to analyze the model of improving Regional Financial Management in West Papua Province based on competence, accountability, organizational commitment and supervisory quality. This study uses a quantitative approach, aiming to test hypotheses, establish facts, describe correlations between variables, offer statistical descriptions, estimate, and forecast results. The population of this study is 5,186 people. The results of the study show that: (1) Human resource competence, accountability and organizational commitment have a positive and significant effect on the quality of supervision, (2) Human resource competence, accountability and organizational commitment have a positive and significant effect on the performance of regional financial management, (3) The quality of supervision has a positive and significant effect on the performance of regional financial management, (4) Human resource competence, accountability and organizational commitment have a significant indirect effect to the performance of regional financial management mediated by the quality of supervision. The higher the competence, accountability and commitment of the organization, the higher the performance of regional financial management mediated by the quality of supervision.